Modification of m5C regulators in sarcoma can guide different immune infiltrations as well as immunotherapy - Wu, Shusheng; Li, Mengge; Su, Rixin; Shen, Hao; He, Yifu; Zhou, Yangfan (Frontiers in Surgery, 2023)
Abstract Background: Recent studies have found that 5-methylcytosine (m5C) modulators are associated with the prognosis and treatment of cancer. However, the relevance of m5C modulators in sarcoma prognosis and the tumour microenvironment is unclear. Methods: We selected 15 m5C regulators and performed unsupervised clustering to identify m5C modification patterns and differentially expressed genes associated with the m5C phenotype in The Cancer Genome Atlas (TCGA) sarcomas. The extent of immune cell infiltration in different clustering groups was explored using single-sample gene set enrichment analysis and estimation algorithms. An m5C scoring scheme based on a principal component analysis algorithm was used to assess the m5C modification patterns of individual tumours. Results: We identified two distinct m5C modification patterns in the TCGA sarcoma cohort, which possess different clinical outcomes and biological processes. Tumour microenvironment analysis revealed two groups of immune infiltration patterns highly consistent with m5C modification patterns, classified as immune inflammatory and immune desert types. We constructed m5C scores and found that high m5C scores were closely associated with leiomyosarcoma and other subtypes, and were associated with poorer prognosis, lower PD-L1 expression, and poorer immunotherapy outcomes. The best application was validated against the m5C database. Conclusion: This study reveals an important link between m5C modifications and the immune microenvironment and survival differences in sarcomas. Assessing the pattern of m5C modification in individual tumours will help improve our understanding of the immune microenvironment in sarcomas.